Development of biomaterials for bone tissue engineering based on bile acids - Yongjun Liu; Xiaojie Liu; Chang Liu; Wenan Zhang; Ting Shi; Guanying Liu (Journal of Materials Science: Materials in Medicine)
Abstract Diseases and injuries can cause significant bone loss, leading to increased medical expenses, decreased work efficiency, and a decline in quality of life. Bone tissue engineering (BTE) is gaining attention as an alternative to autologous and allogeneic transplantation due to the limited availability of donors. Biomaterials represent a promising strategy for bone regeneration, and their design should consider the three key processes in bone tissue engineering: osteogenesis, bone conduction, and bone induction. Certain bile acids (BAs) demonstrate significant antioxidant, anti-inflammatory, and immunosuppressive properties, and effectively promote bone and tissue regeneration. Additionally, the combination of BA molecule with other biological materials can help overcome problems associated with limited local bone regeneration and maintain a defined release state for a long time. Thus in this review, we focus on the role and the mechanism of bile acids in bone healing under different conditions, highlighting their unique properties and applications in gel fabrication, microencapsulation, and nanotechnology. These advancements serve as a basis for the advancement of biomaterials derived from BAs, specifically for the purpose of bone reconstruction. Graphical Abstract